Management of a venous leg ulcer in a resident receiving long-term care: a case study: Obravnava venske golenje razjede pri bolnici v socialnovarstvenem zavodu: študija primera - Medjedović, Sabina (Acta Medico-Biotechnica, 2026)
Purpose: Venous leg ulcers are chronic wounds that are associated with chronic venous insufficiency, which significantly reduces the quality of life in elderly residents and increases the risk of infection and the need for prolonged care.Case Report: We present a case involving an 82-year-old female resident of a long-term care facility with a venous leg ulcer on the left leg. Treatment was administered from April to December 2024 and included wound management according to modern care principles (tissue care, infection/inflammation control, moisture management, and epithelialisation support [TIME]), nursing care planning based on activities of daily living, and multidisciplinary collaboration. Complete wound healing with full granulation and epithelialisation was achieved through individualised local care of the chronic wound, effective exudate management, inflammation and exudate control, nutritional support, appropriate analgesia, and gradual mobilisation as part of physical therapy. At the conclusion of treatment, the pain had resolved, sleep had improved, the fear of limb amputation had decreased, and her psychological well-being had improved.Conclusion: Comprehensive, continuous, and interdisciplinary care of an elderly resident with a venous leg ulcer in an institutional setting can lead to successful healing with appropriate dressing selection, compression therapy, inflammation control, and support with activities of daily living. Key factors for a favourable outcome include realistic goal setting, regular evaluation of treatment progress, and empowerment of the resident and the family.
Keywords: venous leg ulcer; elderly; chronic venous insufficiency; long-term care; chronic wound management